PENGARUH MODEL EXPLICIT INSTRUCTION DALAM PEMBELAJARAN TARI YA SAMAN PADA KEGIATAN EKSTRAKURIKULER DI SMA NEGERI 8 PALEMBANG - Melli Alyana Melli; Efita Elvandari; Nofroza Yelli (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of the explicit instruction model on the learning of Ya Saman dance in extracurricular activities at SMA Negeri 8 Palembang. The research problem focuses on the effectiveness of the explicit instruction learning model in improving students’ learning outcomes in dance instruction. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The population as well as the sample consisted of all students participating in the dance extracurricular activity at SMA Negeri 8 Palembang, totaling 20 students.Data were collected through a practical performance test in the form of a dance performance assessment administered before and after the treatment. The collected data were analyzed using a t-test to examine differences in students’ learning outcomes between the pretest and posttest. The results showed that the mean pretest score was 52.95, while the mean posttest score increased to 77.30. Based on the t-test analysis, the calculated t-value was 7.30, while the t-table value was 2.01. Since the calculated t-value was greater than the t-table value (7.30 > 2.01), the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted.These findings indicate that the application of the explicit instruction model has a significant effect on improving students’ learning outcomes in Ya Saman dance instruction within extracurricular activities at SMA Negeri 8 Palembang. Therefore, the explicit instruction model is considered effective in facilitating students’ understanding and performance of dance movements through a structured and step-by-step learning process.